PENGELOLAAN TAMAN DHARMA WANITA OLEH DINAS KEBERSIHAN DAN PERTAMANAN KOTA PEKANBARU - Hidayat, Suci Lestari; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Research is a method to description about city park management. City park is space the civil society’s necessary in the city as a place to get comfortability and the function of city park as a aesthetic for the city. According to directly observation. The problem is less attention from the government to complement garden’s facility and garden’s maintanance isn’t optimal. Research’s objective is to knowing and analysis Dharma Wanita city park management by departmen of cleanliness and the park in the Pekanbaruand to knowing and analysis hampered factor of Dharma Wanita city park management by cleanliness and the park in the Pekanbaru.The theory is used management that starts from the planning, the organizing, the actuacting and the controlling. The research is used kualitatif method with descriptive data. To get the data, the researcer uses interview, observation, and documentation. The key informan as a infomation source and data analysis.The research gets conclusion that management in departmen of cleanliness and the park management in maintenance city park instead of the planning, the organizing, the actuacting and the controlling. And then hampered factor of Dharma Wanita city park management by departmen of cleanliness and the park in the Pekanbaru in maintenance in city park instead of the budget factor that isn’t enough to completes the city park facility or revitalization. The character factor usage (the society) is less realize and participation to keeping public facility which is given.Keywords : Management, Departmen of Cleanliness, and City Park